2013
DOI: 10.5301/ejo.5000343
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Automatic Biometric Iris Recognition after Phacoemulsification or Drug-Induced Pupil Dilation

Abstract: The results of this trial indicate that standard cataract surgery seems not to be a limiting factor for iris recognition in the large majority of cases. Some patients (5.2% in this study) might need "reenrollment" after cataract surgery. Iris recognition was primarily successful in eyes with medically dilated pupils in nearly 9 out of 10 eyes. No single case of false-positive acceptance occurred in either group in this trial. It seems therefore that iris recognition is a valid biometric method in the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Therefore, glaucoma should be given a description of a multi-factorial optical nerve neuropathy, with increased intraocular pressure being a risk factor [28]. Glaucoma is a second-leading cause of visual impairment and blindness worldwide, secondary to cataracts only [32]. Glaucoma and its impact on iris.…”
Section: Glaucomamentioning
confidence: 99%
“…Therefore, glaucoma should be given a description of a multi-factorial optical nerve neuropathy, with increased intraocular pressure being a risk factor [28]. Glaucoma is a second-leading cause of visual impairment and blindness worldwide, secondary to cataracts only [32]. Glaucoma and its impact on iris.…”
Section: Glaucomamentioning
confidence: 99%
“…A similar scenario regarding the impact of cataract surgery was explored by Seyeddain et al [14] who performed an experiment to establish the effects of phacoemulsification and pharmacologically induced mydriasis on the iris. (Phacoemulsification refers to the extraction of the lens through aspiration.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers carried out an experiment to find out whether such manipulation may result in increased FNMR of an iris biometric system. Using Maseks algorithm for encoding, 13 eyes (out of 14) were correctly recognized after a procedure had been performed. However, the one eye that was falsely non-matched had a significant deviation in circularity of the pupil and increased pupil diameter.…”
Section: Related Workmentioning
confidence: 99%
“…However, numerous medical conditions affecting the eye structures, especially the iris, anterior chamber of the eye, and the cornea, have a potential of degrading its accuracy and reliability. Yet, due to the lack of appropriate datasets and difficulties in creating them, limited research is available, mostly centered around cataract and cataract extraction procedure influence on iris recognition performance: (Roizenblatt et al, 2004), (Seyeddain et al, 2014), (Dhir et al, 2010), (Trokielewicz et al, 2014), (Ramachandra et al, 2016) (significant negative impact of cataract and cataract surgery reported by most researchers except for Dhir et al), impact of refraction correction procedures (Yuan et al, 2007) (no impact reported), but also studies regarding multiple disorders (Aslam et al, 2009), and their impact on segmentation (McConnon et al, 2012). In the papers (Trokielewicz et al, 2015b), we present the most thorough and comprehensive analysis on the subject of disease influence on iris recognition reliability to date, including an extensive cataract influence study, and a novel approach to eye pathology impact analysis, based not on disease taxonomy (impact of certain diseases), but rather on the type of damage that medical disorders afflict on the eye.…”
Section: Iris Biometrics and Ocular Disordersmentioning
confidence: 99%